Hugo Wolf and his Mörike Songs - Youens, Susan (Cambridge Cambridge University Press, 2000)
Viennese composer Hugo Wolf produced one of the most important song collections of the nineteenth century when he set to music fifty-three poems by the great German poet Eduard Mörike. Susan Youens reappraises this singular collaboration, examining selected Mörike songs in detail to shed new light on the sophisticated interplay between poetry and music. Although Wolf is known as "the Poet's Composer," someone who revered poetry and served it faithfully in his music, Youens reveals how his Mörike songs were also influenced by his own life, psychology and experiences.
Keywords: Wolf, Hugo -- 1860-1903; Mörike, Eduard -- 1804-1875; 19th Century (1801-1900); Song; Poetry; Austria